Common ownership in labor markets - José Azar; Yue Qiu; Aaron Sojourner (W.E. Upjohn Institute for Employment Research, 2022)
In this paper, we study the effects of common ownership, the extent to which firms are linked via common owners, on employee earnings in U.S. local labor markets. Between 1999 and 2017, common ownership in local labor markets has more than doubled. Panel regressions show that employee earnings in a local labor market are negatively associated with common ownership. To identify causal effects, we use a firm's addition to the S&P 500 index as a shock to common ownership of its competitors in a local labor market. Using a matched difference-in-differences analysis, we find that, after a firm enters the S&P 500 index, the average annual earnings per employee of its local competitors decreases relative to the counterfactual. The effect of index inclusion shocks on employee earnings is stronger in local labor markets where the shares of S&P 500 incumbents are higher before a shock.
Keywords: J42; J31; L40; D40; G34; 330; Monopsony; oligopsony; labor markets; competition policy; common ownership